Optical coherence tomographic features and visual prognosis after treatment for idiopathic choroidal neovascularization - Cao, Xu-Sheng; Jonas, Jost B. (Ophthalmologica, 2015)
Background: The aim of this study was to determine whether pretreatment spectral-domain optical coherence tomographic (SD-OCT) features are associated with visual